2001
DOI: 10.1089/107632701300003250
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Tissue-Engineered Aortic Valves

Abstract: Tissue-engineered aortic valves, known as recellularized heart valves, were developed by seeding human neonatal fibroblasts onto decellularized, porcine aortic valves. Recellularized heart valves were cultured up to 8 weeks in a novel bioreactor that imposed dynamic pulsatile fluid flow to expose the dermal fibroblasts to mechanical forces. Our data showed that, under static or dynamic flow conditions, dermal fibroblasts attached to and migrated into the decellularized, porcine valve scaffolding. The human cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 45 publications
1
78
0
1
Order By: Relevance
“…Based on these results, decellularized AVs, wherein the interstitial cells have been extracted through tissue decellularization, have been explored as used for valve replacement [15][16][17][18][19][20][21][22]. Decellularized native valve tissues, unlike synthetic scaffold approaches [6,23,24], have the potential to be readily used for AV replacements since they are assumed to have the necessary mechanical strength and the inherent functional design [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, decellularized AVs, wherein the interstitial cells have been extracted through tissue decellularization, have been explored as used for valve replacement [15][16][17][18][19][20][21][22]. Decellularized native valve tissues, unlike synthetic scaffold approaches [6,23,24], have the potential to be readily used for AV replacements since they are assumed to have the necessary mechanical strength and the inherent functional design [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used decellularization methods are a non-ionic detergent, Triton X-100, (tert-octylphenylpolyoxyethylen) [16,21,25], an anionic detergent, SDS (sodium dodecyl sulfate) [20], and an enzymatic agent, Trypsin [15,18,22,26,27]. To understand the mechanics of decellularized valve leaflets, Korossis et al [20] measured the leaflet strips cut along the circumferential or the radial direction and found that after treatment with SDS (hypotonic buffer), extensibility and failure strain of circumferential strips significantly increased, while in the radial strips, there was some increase but not significantly [20].…”
Section: Introductionmentioning
confidence: 99%
“…This preservation of matrix integrity, as well as the efficiency of cell removal is highly dependent on the method used for decellularization [68]. Several different decellularization methodologies for heart valve scaffold fabrication have been reported, including trypsin/ EDTA [68][69][70][71], freeze drying [72], osmotic gradients [73], non-enzymatic detergent treatment [68,74], and multistep enzymatic procedures [75]. The use of non-enzymatic detergent-based techniques has been shown to result in a much more efficient cell removal, while preserving the overall matrix integrity of the scaffold, when compared to other more aggressive decellularization methods such as trypsin/EDTA [68,76,77].…”
Section: Decellularized Tissue-derived Matrices: the Biologic Countermentioning
confidence: 99%
“…This need is being met by several approaches to functional tissue engineering of heart valve replacements. [1][2][3][4][5][6] As these technologies progress, it is likely important that replacement tissues mimic the multiaxial mechanical behavior of native aortic valve tissues.…”
Section: Introductionmentioning
confidence: 99%